LOAD PLANNING IN THE PROCESS OF PHYSICAL EDUCATION OF STUDENTS WITH VISUAL IMPAIRMENTS (EDUCATION IN THE 21ST CENTURY, 2025)
This article reveals the basic factors, signs, and indicators of tiredness to be obligatory considerations in the process of organizing and conducting physical activities with students with different types of visual impairment. As the different forms and degrees of visual impairment, psychophysical peculiarities of development, and lack of development of motor skills and orientations in space of those students determine the importance and necessity of using protective means and mobilizing stand-by resources at gym classes. It has been established that deep and partial visual impairment significantly impedes the motor possibilities of students, their orientation in macro- and micro-spaces, their understanding of the teaching material of physical education programs, and their participation in physical and sport activities. Therefore, in order to prevent injuries and further visual impairments in students during physical activities in school, university, and gyms, we have to take into account the gender, form, and degree of visual impairment; the availability of concomitant diseases; secondary developmental deviations; the level of physical preparedness of students; and many other factors. This will serve as the basis for health strengthening in students with different types of visual impairment. The abovementioned points define the relevant, theoretical, and practical significance of the present research theme.
Keywords: students, special education department; education; physical load; forms and degrees of developmental disorders; load regulation